Fluorine in the environment, a review of its sources and geochemistry - Fuge, Ron (Applied geochemistry, 2019)
While F is an essential constituent of some rock-forming minerals such as fluorite and apatite, its major occurrence in the lithosphere is within hydroxysilicate minerals where F− occupies OH− lattice sites. The majority of the F occurring in the secondary environment derives from natural weathering processes with some soils derived from F-rich parent rocks containing over 1weight (wt) % F. Other natural sources of F are vulcanicity, wind-blown dust and a minor marine-derived component, with biomass burning, being in part natural, also a source. Several anthropogenic sources of environmental F have also been identified. Of the anthropogenic sources, the application of phosphate fertiliser, which probably adds over 2.3 Mt a−1 F to soils globally, represents the largest. While much of this is strongly retained in soils, some may be transferred to groundwater. In some abandoned mine sites in the UK where fluorite was associated with the mineralisation, soil F contents of up to 8 wt % have been recorded with plants growing on the sites containing up to 1wt % F. The rapid growth of urban areas in India, Pakistan and Bangladesh has resulted in an upsurge of brickmaking in Asia, with these 3 countries plus China accounting for over 75% of global brick production. As a result there is a large number of unregulated brick kilns which emit HF into the surrounding environment. Based on an annual global brick production of 1500 billion and the F contents of brick clays, it is estimated that about 1.8 Mt a−1 F are released to the environment from brick manufacture. This suggests that brickmaking is the largest source of atmospheric F emissions dwarfing that of coal combustion, 0.2–0.3 Mt a−1, phosphate fertiliser production, 0.07–0.10 Mt a−1, aluminium smelting, 0.041 Mt a−1, and even vulcanicity, 0.3–0.7 Mt a−1. However, it is apparent that atmospheric F emissions are not transported globally and as such their effects are manifested only in the local environment. Emissions from industry sited close to urban centres can impact these environments together with domestic coal combustion and the release of F from high octane fuels in motor vehicles. A more recent source of F in the environment stems from the large number of fluorocarbon compounds in everyday use. Degradation of some of these fluorocarbon compounds together with pyrolysis of fluoropolymers and burning of household refuse has resulted in the deposition of organofluorine compounds such trifluoroacetic acid in the environment. •The majority of the F occurring in the secondary environment derives from natural weathering processes.•The application of phosphate fertiliser is the largest anthropogenic source of F in the environment, probably adding over 2.3 Mt a−1 F to soils globally.•Global brick production is estimated to release about 1.8 Mt a−1 F, making it the largest source of F emissions to the atmosphere.•Other anthropogenic sources of F emissions to the atmosphere are coal combustion, 0.2–0.3 Mt a−1, phosphate fertiliser production, 0.07–0.10 Mt a−1 and aluminium smelting, 0.041 Mt a−1.•Vulcanicity has been estimated to release 0.3–0.7 Mt a−1to the atmosphere.